Effects of sildenafil, metformin, and simvastatin on ADH‐independent urine concentration in healthy volunteers. Issue 7 (2nd April 2018) - Bech, Anneke P.; Wetzels, Jack F. M.; Nijenhuis, Tom
Abstract: Nephrogenic diabetes insipidus (NDI) is a rare disorder characterized by resistance of the kidney to the action of antidiuretic hormone (ADH), resulting in a decrease in the capacity of the kidney to concentrate the urine. NDI can be inherited or acquired due to, for example, chronic lithium therapy. Current treatment options are limited to attempts to lower urine output by a low‐solute diet and the use of diuretics or anti‐inflammatory drugs. These measures are only partially effective. Recent reports suggested that sildenafil, metformin, and simvastatin might improve ADH‐independent urine concentration. If confirmed, this would provide interesting additional therapeutic options for patients with NDI. We, therefore, tested the effect of these drugs on ADH‐independent urine concentrating capacity in healthy volunteers. We included 36 healthy volunteers who received sildenafil 20 mg thrice daily, metformin 500 mg thrice daily or simvastatin 40 mg once daily during 1 week. At baseline and at the end of treatment, a water loading test was performed. No significant increase in lowest urine osmolality was seen after the use of metformin or sildenafil ( P  = 0.66 and P  = 0.09 respectively). Lowest urine osmolality increased modestly but significantly after the use of simvastatin (70 mOsm/kg to 85 mOsm/kg, P  = 0.05). Our data suggest that only simvastatin has an effect on urine osmolality in healthy volunteers. Validation studies are needed and, most importantly, these drugs should be tested in patients with NDI. Abstract : Recent reports suggested that sildenafil, metformin, and simvastatin might improve ADH‐independent urine concentration. Our data suggest that only simvastatin has an effect on urine osmolality in healthy volunteers. Validation studies are needed and, most importantly, these drugs should be tested in patients with NDI.